2013
DOI: 10.1155/2013/754564
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic Assessment of Females with Carpal Tunnel Syndrome Proved by Nerve Conduction Study

Abstract: Introduction. Carpal tunnel syndrome (CTS) is the most commonly diagnosed entrapment neuropathy of the upper extremity. The objective of this study was to diagnose CTS and to assess its severity using high resolution ultrasound (HRUS) depending on the results of nerve conduction study (NCS). Methods. A prospective cross-sectional study, in which HRUS was performed at 63 wrists of 35 female patients with different severity of CTS (as proved by NCS). Furthermore, 40 healthy volunteers (80 wrists) underwent the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 29 publications
(39 reference statements)
0
17
0
Order By: Relevance
“…Several studies have confirmed the feasibility of distal CSA measurement of the median nerve not only in the diagnosis of CTS, but also in the grading of CTS severity [9,[24][25][26][27], especially when using the ratio measurement [8][9][10]. Fig.…”
Section: Discussionmentioning
confidence: 94%
“…Several studies have confirmed the feasibility of distal CSA measurement of the median nerve not only in the diagnosis of CTS, but also in the grading of CTS severity [9,[24][25][26][27], especially when using the ratio measurement [8][9][10]. Fig.…”
Section: Discussionmentioning
confidence: 94%
“…6 In this study, NCS of the MN were used as a valuable technique for the diagnosis and subdivision of patient group into the following three groups: mild, moderate, and severe CTS. 6 In this study, NCS of the MN were used as a valuable technique for the diagnosis and subdivision of patient group into the following three groups: mild, moderate, and severe CTS.…”
Section: Discussionmentioning
confidence: 99%
“…3 However, NCS have several limitations because they are uncomfortable for many patients. [6][7][8][9] Several studies have noted that increases in the crosssectional area (CSA) of the median nerve (MN) in the wrist are the most reliable finding in the diagnosis of CTS. 4 By contrast, high-resolution ultrasonography (HRUS) is a quick and painless procedure that sheds light on the anatomy 5 and potentially the etiology of the pathology causing CTS.…”
mentioning
confidence: 99%
“…[ 21 ] US could be used to grade the severity of CTS and to detect space-occupying lesions or anatomical variation of median nerve. [ 17 ] In the present study, it was possible to correlate HRUS findings and EDX findings based on CTS grading. It showed that the accuracy of HRUS was similar to that for EDX in all grades of CTS and CTS + PNP in patients with a clinical diagnosis of CTS.…”
Section: Discussionmentioning
confidence: 95%
“…There are many studies emphasizing the role of imaging in the diagnosis of CTS. [ 13 14 15 16 17 ] It has been shown that high-resolution ultrasonography (HRUS) is very useful where EDX has been equivocal and in assessment of recurrent or unrelieved symptoms after surgical carpal tunnel release. A reliable diagnosis of CTS could be made sonographically, mainly based on an increase in cross-sectional area (CSA) of the median nerve at the level of the Pisiform or Hamate bone.…”
Section: Introductionmentioning
confidence: 99%